ANALYSIS REPORT FINANCE PT. TELKOM INDONESIA (LIMITED) TBK 2023-2024 PERIOD - Dea Amanda; Miftahul Jannah; Nabila Nur Ayuni Balqis; Toha; Aiyub (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study aims to evaluate the financial performance of PT Telkom Indonesia (Persero) Tbk during the 2023-2024 period using financial ratio analysis. As the largest state-owned telecommunications company, Telkom faces the challenges of digital transformation and dynamic market competition. The research method used is descriptive comparative, processing secondary data from the company's annual financial reports, including the balance sheet and income statement. The analysis results show that the company's liquidity has improved, as evidenced by the Current Ratio, which rose from 0.78 to 0.82, although still below the ideal standard. In terms of solvency, the company maintains a healthy capital structure with a Debt to Asset Ratio (DAR) of 46%. However, profitability is under pressure, with a decline in Net Profit Margin (NPM) to 20.5% due to increased operating expenses. The activity ratio also recorded a slowdown in accounts receivable turnover to 12.30 times. Overall, Telkom has strong financial fundamentals but needs to improve operational efficiency and optimize accounts receivable collection to maintain future growth.